Physical Education and ideology. Pedagogical beliefs and cultural domination in the school education of the body - Miguel Vicente Pedraz (FEADEF, 2010)
This article addresses the political and ideological dimension of physical education. The didactic discourse more specific of physical education, as a school subject, relies upon the technical relationship between pedagogical means and ends, and, therefore, offers a rather neutrally ideological image of those social representations that most define the body as an organic and anatomic structure. The belief in the substantiality of the body and in physical education as an academic discipline itself has shaped a large series of educational structures as well as a whole body of arguments and practices, all meant to convert physical education in a discipline virtually above any attempt of criticism, except for certain superficial matters, rather paradoxical and, probably, hardly acceptable in other disciplines and educational contexts. With these assumptions, the objective of the article is to discuss some of the mechanisms of construction of these beliefs, to identify the power relations that sustain these mechanisms and to question the deficiency of practical sense of the curriculum that as a result legitimizes the technical discourse.